(untitled) (Gremium, 2020)
All over the world there is a vast heritage of earth construction where earth plasters were applied. Nowadays, dueto environmental but also technical reasons, new earth plasters are also applied on common new masonries. That is why its characterization, in the laboratory but also in situ, is very important. In the present study, a pre-mixed earth plastering mortar (as control) and nine earth-based plastering mortars formulated in laboratory withdifferent compositions were characterized. These mortars were formulated with 1:3 (illitic clayish earth:aggregate)volumetric ratio. The aggregate comprises a variation of fine and coarse sand and the partial replacement of thefine sand by a phase change material (PCM). The influence of the addition of a low amount of oat fibers is alsoevaluated. The mortars were characterized by different methods in laboratory and on an experimental wall exposedoutdoors by destructive and nondestructive methods: dry bulk density, dynamic modulus of elasticity, flexural andcompressive strengths, adhesive and shear strengths, dry abrasion resistance, surface cohesion, ultrasonic pulsevelocity and hardness. Results were discussed and some were correlated. Most mortars present good mechanicalstrengths. However, the addition of PCM significantly decrease the mechanical strength of mortars. In terms ofmechanical properties, the addition of oat fibers only promotes an improvement on adhesive strength. The simplesurface hardness by durometer presents laboratory and in situ results well correlated for earth mortars withoutPCM.